A modified styrene-acrylic emulsion and preparation method thereof

By using the polymerization technology of perfluoropolyether carboxylate and carbon quantum dot-titanium dioxide composite in styrene emulsion, the problems of insufficient performance and uneven dispersion of nanoparticles in the existing styrene emulsion are solved, and higher stability and corrosion resistance are achieved, while meeting environmental protection requirements.

CN112538140BActive Publication Date: 2025-05-02NORTH & SOUTH BROTHER PHARMACY INVESTMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011036919.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-09-28
Publication Date
2025-05-02
Estimated Expiration
2040-09-28

AI Technical Summary

Technical Problem

The existing styrene acrylic emulsions have shortcomings in terms of antioxidant, dilation, water resistance, etc., and nanoparticles are difficult to disperse uniformly in the emulsion, affecting their performance and environmental friendliness.

Method used

Perfluoropolyether carboxylate and carbon quantum dot-titanium dioxide composite are polymerized in styrene emulsion to form an emulsion coating with denser structure and strengthened chemical bonds, improving its stability and corrosion resistance.

Benefits of technology

It significantly improves the stability, wear resistance and corrosion resistance of styrene acrylic emulsion, and meets environmental protection requirements, avoiding the problem of uneven dispersion of nanoparticles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002705349510000061
    Figure BDA0002705349510000061
Patent Text Reader

Abstract

The present invention relates to a modified styrene-acrylic emulsion and a preparation method thereof. Specifically, the present invention provides a modified styrene-acrylic emulsion, which is prepared by polymerization reaction of acrylate, styrene, acrylic acid, acrylamide, perfluoropolyether methacrylate and carbon quantum dot-titanium dioxide composite under the action of an initiator and an emulsifier. By adding perfluoropolyether methacrylate, the emulsion is given better film-forming properties; by adding the carbon quantum dot-titanium dioxide composite and compounding with other components, the stability, corrosion resistance and wear resistance of the styrene-acrylic emulsion are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to a modified styrene-acrylic emulsion and a preparation method thereof. Background Art

[0002] Styrene acrylic emulsion is made by polymerizing acrylate monomers and styrene, and is widely used in metal coatings, building materials coatings, adhesives, etc. However, styrene acrylic emulsion is still not perfect in terms of anti-oxidation, expansion, water resistance, etc., which greatly limits its scope of application.

[0003] The prior art usually modifies it, for example, using organic fluorine for improvement. Commonly used fluorine-containing monomers are propylene trifluoroacetate, hexafluorobutyl methacrylate, dodecafluoroheptyl methacrylate, perfluoroalkyl ethyl acrylate or perfluoroalkyl ethyl methacrylate, which improves the performance of styrene acrylic emulsion to a certain extent, but there are still problems such as emulsion stability, hardness, corrosion resistance and other properties that cannot meet the requirements; in addition, due to the disadvantages of perfluoroalkyl long-chain acrylate polymers being difficult to degrade and easy to bioaccumulate, it has an adverse impact on the environment and its use will also be restricted. Another example is the use of nano-modification to diffuse nanoparticles in the emulsion, giving full play to the advantages of organic molecules and inorganic molecules, but the main problem is that the nanoparticles cannot be evenly dispersed in the styrene acrylic emulsion.

[0004] It is reported that perfluoropolyether has no bioaccumulation, which may be due to the involvement of oxygen atoms in the polyether chain, so that perfluoropolyether does not have a dense fluorine shell like perfluoroalkane, and small molecules can easily enter the main chain and are easily degraded, without potential teratogenic and carcinogenic hazards to organisms. The prior art on perfluoropolyether carboxylates is mainly used in the field of fabric finishing agents to give fabrics better water and oil resistance, and there are no reports on styrene acrylic emulsions or improving the stability and corrosion resistance of styrene acrylic emulsions.

[0005] Carbon quantum dots (CDs or CQDs) are usually spherical particles with a diameter of less than 10nm, composed of sp2 / sp3 carbon clusters with amorphous or nanocrystalline structures. They have a variety of excellent optical properties, such as optical absorption, photoluminescence, chemiluminescence and electrochemiluminescence, which make them have great potential application value in the fields of biology, medicine, chemical engineering, electronics, etc. CDs are usually compounded with TiO2 to make CDs-TiO2 photocatalysts. On the one hand, the material has low toxicity, which overcomes the disadvantage of high toxicity of traditional quantum dots; on the other hand, it can effectively inhibit the recombination of photogenerated electrons and holes, enhance the absorption of ultraviolet light and expand the absorption of visible light and even near-infrared light, thereby improving the photocatalytic activity of the material; there are no reports on the application of CDs in styrene-acrylic emulsions or improving the stability and corrosion resistance of styrene-acrylic emulsions.

[0006] The modification research of styrene acrylic emulsion needs to be continued. Summary of the invention

[0007] In order to solve at least one of the above problems, the present invention provides a modified styrene-acrylic emulsion and a preparation method thereof, so as to obtain a styrene-acrylic emulsion with excellent performance. On the one hand, perfluoropolyether carboxylate is used, and through polymerization with other components of the present invention, not only better film-forming properties are given to the emulsion, but also environmental protection requirements are met; on the other hand, the carbon quantum dot-titanium dioxide composite used has a spherical structure and a specific size, can be evenly dispersed in the emulsion, and through the reaction of multiple functional groups with other components, a strong chemical bond is formed, so that the emulsion coating has a denser structure and the stability of the emulsion is enhanced; the present invention realizes the composite of nanoparticle carbon quantum dot-titanium dioxide composite and other components, which can effectively improve the stability and corrosion resistance of the emulsion.

[0008] In some embodiments, the modified styrene-acrylic emulsion of the present invention is prepared by polymerization reaction of acrylate, styrene, acrylic acid, acrylamide, perfluoropolyether methacrylate and carbon quantum dot-titanium dioxide composite under the action of an initiator and an emulsifier;

[0009] The acrylic acid ester is methyl methacrylate, ethyl methacrylate, methyl acrylate or ethyl acrylate;

[0010] The acrylamide is N-hydroxyethyl acrylamide, N-hydroxymethyl acrylamide or N,N'-methylenebisacrylamide;

[0011] The molecular formula of the perfluoropolyether methacrylate is [CF(CF3)CF2O] n -CH2-O-COC(CH3)=CH2;

[0012] The carbon quantum dot-titanium dioxide composite is composed of dispersed spherical carbon particles with a size of less than 10 nm;

[0013] The initiator is sodium persulfate, potassium persulfate, ammonium persulfate, azobisisobutyronitrile, azobisisobutyramidine hydrochloride, azobisisobutylimidazoline hydrochloride or 2,2-azobis(2-methylpropylimidazole) dihydrochloride;

[0014] The emulsifier is a combination of isomeric tridecanol polyoxyethylene ether, sorbitan fatty acid ester and Tween-20.

[0015] In some embodiments, the weight average molecular weight of the perfluoropolyether methacrylate of the present invention is 1000-3000.

[0016] The weight average molecular weight of the perfluoropolyether methacrylate is preferably 1500-2000. The perfluoropolyether methacrylate with a suitable molecular weight is selected in the present invention to give the modified styrene-acrylic emulsion better film-forming properties through polymerization with other monomers of the present invention.

[0017] Preferably, the amount of the perfluoropolyether methacrylate in the modified styrene acrylic emulsion is 10-15 wt %.

[0018] In some of the embodiments, the carbon quantum dots of the present invention can be synthesized by known conventional methods, such as electrochemical synthesis, chemical oxidation, combustion, hydrothermal synthesis, solvent thermal synthesis, microwave synthesis, etc.

[0019] Preferably, the carbon quantum dots of the present invention are prepared by hydrothermal method using carbon source and water as raw materials; the carbon source can come from fruit juice, milk, egg white, vitamin C, glucose, sucrose, etc. The specific preparation method is: mixing the carbon source with water, reacting at 100-250°C for 4-10h, cooling, centrifuging and taking the supernatant to obtain a solution containing carbon quantum dots.

[0020] The carbon quantum dot-titanium dioxide composite of the present invention can be obtained by using carbon quantum dots (or a solution containing carbon quantum dots) and titanium dioxide as raw materials and by using existing conventional methods.

[0021] Preferably, the carbon quantum dot-titanium dioxide composite of the present invention is prepared by the following method: fully mixing carbon quantum dots (or a solution containing carbon quantum dots), titanium dioxide and water, and then fully drying. The present invention further preferably comprises: stirring and ultrasonic treatment; the degree and time of stirring and ultrasonic treatment are sufficient to ensure that the carbon quantum dots and titanium dioxide are fully dispersed, mixed and dissolved in water. The present invention further preferably comprises: drying at 60-100°C under vacuum conditions for 5-20 hours.

[0022] The present invention shows that the carbon quantum dot-titanium dioxide composite has unique properties, such as rich functional groups such as carboxyl and hydroxyl groups on the surface, non-toxic, good biocompatibility, easy functional modification, unique size and morphology, less than 10nm in size, and composed of dispersed spherical carbon particles; therefore, the carbon quantum dot-titanium dioxide composite reacts with other components through multiple functional groups to form a strong chemical bond, so that the emulsion coating has a denser structure, and can play the rigid role of the carbon quantum dot-titanium dioxide composite, thereby enhancing the stability and wear resistance of the modified styrene-acrylic emulsion. Compared with the use of titanium dioxide alone, it avoids the undesirable problems such as serious agglomeration, poor stability, easy stratification, and easy sedimentation.

[0023] In addition, titanium dioxide can shield ultraviolet rays, prevent ultraviolet damage, and extend the service life of the lotion.

[0024] Preferably, the amount of the carbon quantum dot-titanium dioxide composite in the modified styrene-acrylic emulsion is 2-6wt%; more preferably, the amount of the carbon quantum dot-titanium dioxide composite in the modified styrene-acrylic emulsion is 4-6wt%. If the amount of the carbon quantum dot-titanium dioxide composite is too low, the wear resistance and corrosion resistance of the modified styrene-acrylic emulsion cannot be significantly improved; if the amount is too high, it cannot effectively bond with other components, which is not conducive to the stability of the emulsion.

[0025] Most preferably, the mass ratio of the emulsifier of the present invention is isomeric tridecanol polyoxyethylene ether: sorbitan fatty acid ester: Tween-20=1:1:1; within this ratio range, the emulsification effect is good and the polymerization effect is the highest.

[0026] In the prior art, there are various types of emulsifiers, including but not limited to sodium dodecyl sulfate (SDS), sodium dodecylbenzene sulfonate (K-12), sodium vinyl sulfonate (SVS), sodium alkylamide vinyl sulfonate (DNS-86), sodium methyl allyl hydroxypropane sulfonate (HPMAS), sodium allyloxy hydroxypropane sulfonate (HAPS), hexadecyl trimethyl ammonium bromide (CTAB), isomeric tridecanol polyoxyethylene ether, polyethylene glycol octylphenyl ether, acrylic acid polyether phosphate, etc. Conventional emulsifiers have poor emulsification effect, poor dispersion of emulsion droplets, large emulsion droplets, and are very easy to break the emulsion and produce gel during the polymerization process.

[0027] The emulsifier of the present invention is a combination of three emulsifiers. Compared with the prior art, on the one hand, it has a better emulsification effect, the particle size of the latex micelles formed during the polymerization process is small, and the polymerization rate can be increased. On the other hand, the modified styrene-acrylic emulsion of the present invention has better stability.

[0028] Preferably, the amount of the emulsifier in the modified styrene-acrylic emulsion is 0.1-1.5wt%. The present invention shows that when the amount of the emulsifier is low, the emulsification effect cannot be achieved. As the amount of the emulsifier increases, the monomer conversion rate increases. When the amount of the emulsifier is further increased, for example, when it exceeds 1.5wt%, gel begins to form in the polymer, which affects the film-forming property of the emulsion. More preferably, the amount of the emulsifier in the modified styrene-acrylic emulsion is preferably 0.3-0.9wt%, which can comprehensively consider the polymerization performance and emulsion performance.

[0029] In one embodiment, the modified styrene-acrylic emulsion of the present invention is composed of the following components in parts by mass: 10-20 parts of acrylate, 10-25 parts of styrene, 0.1-1.5 parts of acrylic acid, 0.1-5 parts of acrylamide, 8-20 parts of perfluoropolyether methacrylate, 2-6 parts of carbon quantum dot-titanium dioxide composite, 0.05-1 parts of initiator, 0.1-1.5 parts of emulsifier, and the balance is water, and the sum of the parts by mass of each component is 100 parts.

[0030] In another embodiment, the modified styrene-acrylic emulsion of the present invention is composed of the following components in parts by mass: 10-20 parts of acrylate, 15-20 parts of styrene, 0.5-1 part of acrylic acid, 0.5-3 parts of acrylamide, 10-15 parts of perfluoropolyether methacrylate, 4-6 parts of carbon quantum dot-titanium dioxide composite, 0.1-0.5 parts of initiator, 0.1-1 parts of emulsifier, and the remainder is water, and the sum of the parts by mass of each component is 100 parts.

[0031] Preferably, the modified styrene-acrylic emulsion of the present invention is composed of the following components in parts by mass: 10-20 parts of acrylate, 15-20 parts of styrene, 0.5-0.9 parts of acrylic acid, 0.8-2.6 parts of N-hydroxymethyl acrylamide, 10-15 parts of perfluoropolyether methacrylate, 4-6 parts of carbon quantum dot-titanium dioxide composite, 0.1-0.5 parts of initiator, 0.3-0.9 parts of emulsifier, and the balance is water, and the sum of the parts by mass of each component is 100 parts.

[0032] On the other hand, the present invention provides a method for preparing a modified styrene-acrylic emulsion, comprising the following steps:

[0033] S1: emulsifying 1 / 3 of the emulsifier, deionized water, methyl methacrylate, styrene, acrylic acid, acrylamide, perfluoropolyether methacrylate and carbon quantum dot-titanium dioxide composite by a high-pressure homogenizer for 45-100 minutes to obtain a pre-emulsion;

[0034] S2: Add the remaining 2 / 3 of the emulsifier and 1 / 2 of the initiator into deionized water, raise the temperature to 60-90°C, then drop the pre-emulsion and the remaining 1 / 2 of the initiator to carry out a polymerization reaction to obtain a modified styrene-acrylic emulsion.

[0035] Compared with the prior art, the present invention has the following beneficial effects: (1) the excellent properties of perfluoropolyether are introduced into styrene acrylic emulsion, and through polymerization with other components of the present invention, the emulsion is not only endowed with better film-forming properties, but also meets environmental protection requirements; (2) the carbon quantum dot-titanium dioxide composite is added to the styrene acrylic emulsion, thereby enhancing the stability of the emulsion; (3) a strong bonding between the carbon quantum dot-titanium dioxide composite and other components is achieved, which can effectively improve the stability, corrosion resistance and wear resistance of the emulsion. DETAILED DESCRIPTION

[0036] The present invention can be better understood through the following examples, but the present invention is by no means limited to the following examples. The raw materials and equipment used in the present invention can be purchased from the market or are commonly used in the art, wherein the emulsifier is isomeric tridecanol polyoxyethylene ether, anhydrous sorbitan fatty acid ester and Tween-20, and the mass ratio is 1:1:1; the methods in the embodiments, unless otherwise specified, are all conventional methods in the art.

[0037] Preparation of Carbon Quantum Dots-TiO2 Composites

[0038] Preparation Example 1

[0039] Dissolve 0.60 g of sucrose in 40 mL of deionized water, stir to dissolve the sucrose, pour the solution into a reactor, place it in an oven at 130 ° C for 4.5 h, cool naturally, and centrifuge to obtain the supernatant, which is the carbon quantum dot solution (CQDs);

[0040] Take 30 mL of carbon quantum dot solution, add 45 mL of deionized water and 3 g of TiO2, stir the mixture magnetically for 2.5 h, ultrasonically treat for 2 h, filter and transfer the product to a vacuum drying oven at 80 °C and dry for 12 h to obtain a CQDs / TiO2 composite.

[0041] Preparation Example 2

[0042] Dissolve 0.60 g of sucrose in 40 mL of deionized water, stir to dissolve the sucrose, pour the solution into a reactor, place it in an oven at 160 ° C for 8 h, cool naturally, and centrifuge to obtain the supernatant, which is the carbon quantum dot solution (CQDs);

[0043] Take 30 mL of carbon quantum dot solution, add 45 mL of deionized water and 3 g of TiO2, stir the mixture magnetically for 4.5 h, treat it ultrasonically for 1.5 h, filter it, transfer it to a vacuum drying oven at 80 °C and dry it for 12 h to obtain a CQDs / TiO2 composite.

[0044] Example 1

[0045] 30 mL of deionized water was added to a 500 mL three-necked flask, and 0.3 g of an emulsifier was added, and the mixture was slowly stirred at a uniform speed; 20 g of methyl methacrylate, 15 g of styrene, 0.5 g of acrylic acid, 0.8 g of N-hydroxymethyl acrylamide, 10 g of perfluoropolyether methacrylate (weight average molecular weight 1600) and 4 g of the carbon quantum dot-titanium dioxide composite of Preparation Example 1 were added in sequence, and the mixture was emulsified with a high-pressure homogenizer for 45 min to obtain a pre-emulsion;

[0046] 0.6 g of emulsifier and 0.15 g of potassium persulfate were mixed in 18.5 mL of deionized water, and the temperature was raised to 80°C. The pre-emulsion and 0.15 g of potassium persulfate were added dropwise. The pre-emulsion was added dropwise for 2 h, and the initiator aqueous solution was added dropwise for 3 h to carry out polymerization reaction to obtain a modified styrene-acrylic emulsion.

[0047] Example 2

[0048] 30 mL of deionized water was added to a 500 mL three-necked flask, 0.1 g of an emulsifier was added, and the mixture was slowly stirred at a uniform speed; 10 g of ethyl methacrylate, 20 g of styrene, 0.7 g of acrylic acid, 1.5 g of N-hydroxyethyl acrylamide, 12 g of perfluoropolyether methacrylate (weight average molecular weight 2000) and 5 g of the carbon quantum dot-titanium dioxide composite of Preparation Example 1 were added in sequence, and the mixture was emulsified with a high-pressure homogenizer for 60 min to obtain a pre-emulsion;

[0049] 0.2 g of emulsifier and 0.25 g of ammonium persulfate were mixed in 20 mL of deionized water, the temperature was raised to 80°C, and the pre-emulsion and 0.25 g of ammonium persulfate were added dropwise. The pre-emulsion was added dropwise for 2 h, and the initiator aqueous solution was added dropwise for 3 h to carry out polymerization reaction to obtain a modified styrene-acrylic emulsion.

[0050] Example 3

[0051] 30 mL of deionized water was added to a 500 mL three-necked flask, and 0.2 g of an emulsifier was added, and the mixture was slowly stirred at a uniform speed; 15 g of methyl acrylate, 15 g of styrene, 0.9 g of acrylic acid, 2.6 g of N,N'-methylenebisacrylamide, 15 g of perfluoropolyether methacrylate (weight average molecular weight 2000) and 6 g of the carbon quantum dot-titanium dioxide composite of Preparation Example 2 were added in sequence, and the mixture was emulsified with a high-pressure homogenizer for 75 min to obtain a pre-emulsion;

[0052] 0.4 g of emulsifier and 0.05 g of potassium persulfate were mixed in 14.8 mL of deionized water, and the temperature was raised to 80°C. The pre-emulsion and 0.05 g of potassium persulfate were added dropwise. The pre-emulsion was added dropwise for 4 h, and the initiator aqueous solution was added dropwise for 6 h to carry out polymerization reaction to obtain a modified styrene-acrylic emulsion.

[0053] Comparative Example 1

[0054] In Comparative Example 1, the carbon quantum dot-titanium dioxide composite is replaced with nano-titanium dioxide, and the rest is the same as in Example 3.

[0055] Comparative Example 2

[0056] In Comparative Example 2, the carbon quantum dot-titanium dioxide composite was replaced with quantum dot-filled aminofullerene, and the rest was the same as in Example 3; wherein the preparation method of the quantum dot-filled aminofullerene was as follows: 10 g of the carbon quantum dots and 0.01 mol of aminofullerene obtained in Preparation Example 2 were ultrasonically dispersed in 100 mL of 95% ethanol solution for 2 hours at an ultrasonic power of 1 KW.

[0057] Performance Testing

[0058] Static stability test: The emulsion was left to stand at room temperature for 1 month and the state of the emulsion was observed.

[0059] Thermal stability test: The emulsion was placed at 80°C for 4 hours and the emulsion state was observed; then the emulsion state was slowly restored to room temperature and the emulsion state was observed.

[0060] Centrifugal stability test: Take 5 mL of the emulsion and centrifuge it at 3000 r / min for 15 min to observe the state of the emulsion.

[0061] Corrosion resistance test: After being naturally dried for one week, the latex film was immersed in 5% hydrochloric acid, 5% NaOH, and 3% salt water, respectively, and the surface state changes of the latex film and the corrosion resistance time were observed and recorded.

[0062] Wear resistance test: The coating wear resistance test is carried out in accordance with GB / T4893.8-2013. The coated sample is tested using a paint film abrasion tester with a working disk speed of 60r / min. After 200 revolutions, the degree of wear is measured, where level 1 indicates whitening, level 2 indicates slight local whitening, level 3 indicates obvious local whitening, and level 4 indicates severe whitening.

[0063] Table 1 Performance test results

[0064]

[0065] It can be seen from the test results in Table 1 that the modified styrene acrylic emulsion prepared by the present invention has better thermal stability, centrifugal stability, wear resistance and acid / alkali / salt corrosion resistance. Compared with the prior art, the presence of the carbon quantum dot-titanium dioxide composite has a greater impact on the performance of the emulsion and can significantly enhance the stability, wear resistance and corrosion resistance of the emulsion.

[0066] The present invention is not limited to the above-mentioned embodiments and the specific details in the above-mentioned embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A modified styrene-acrylic emulsion, characterized in that: The modified styrene-acrylic emulsion is prepared by polymerization reaction of acrylate, styrene, acrylic acid, acrylamide, perfluoropolyether methacrylate and carbon quantum dot-titanium dioxide composite under the action of initiator and emulsifier; Wherein, the acrylic acid ester is methyl methacrylate, ethyl methacrylate, methyl acrylate or ethyl acrylate; The acrylamide is N -Hydroxyethyl acrylamide, N - Hydroxymethyl acrylamide or N , N '-Methylenebisacrylamide; The weight average molecular weight of the perfluoropolyether methacrylate is 1000-3000; The initiator is sodium persulfate, potassium persulfate, ammonium persulfate, azobisisobutyronitrile, azobisisobutyramidine hydrochloride, azobisisobutylimidazoline hydrochloride or 2,2-azobis(2-methylpropylimidazole) dihydrochloride; The emulsifier is a combination of isomeric tridecanol polyoxyethylene ether, sorbitan fatty acid ester and Tween-20; The mass ratio of the isomeric tridecanol polyoxyethylene ether, sorbitan fatty acid ester and Tween-20 is 1:1:

1.

2. The modified styrene-acrylic emulsion according to claim 1, characterized in that: The modified styrene-acrylic emulsion is composed of the following components in parts by mass: 10-20 parts of acrylate, 10-25 parts of styrene, 0.1-1.5 parts of acrylic acid, 0.1-5 parts of acrylamide, 8-20 parts of perfluoropolyether methacrylate, 2-6 parts of carbon quantum dot-titanium dioxide composite, 0.05-1 parts of initiator, 0.1-1.5 parts of emulsifier, and the balance is water, and the sum of the parts by mass of each component is 100 parts.

3. The modified styrene-acrylic emulsion according to claim 1, characterized in that: The modified styrene-acrylic emulsion is composed of the following components in parts by mass: 10-20 parts of acrylate, 15-20 parts of styrene, 0.5-1 part of acrylic acid, 0.5-3 parts of acrylamide, 10-15 parts of perfluoropolyether methacrylate, 4-6 parts of carbon quantum dot-titanium dioxide composite, 0.1-0.5 parts of initiator, 0.1-1 parts of emulsifier, and the balance is water, and the sum of the parts by mass of each component is 100 parts.

4. The modified styrene-acrylic emulsion according to claim 1, characterized in that: The modified styrene-acrylic emulsion is composed of the following components in parts by mass: 10-20 parts of acrylate, 15-20 parts of styrene, and 0.5-0.9 parts of acrylic acid. N -0.8-2.6 parts of hydroxymethyl acrylamide, 10-15 parts of perfluoropolyether methacrylate, 4-6 parts of carbon quantum dot-titanium dioxide composite, 0.1-0.3 parts of initiator, 0.3-0.9 parts of emulsifier, and the balance is water. The sum of the mass parts of each component is 100 parts.

5. The method for preparing the modified styrene-acrylic emulsion according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1: emulsifying 1 / 3 of the emulsifier, deionized water, methyl methacrylate, styrene, acrylic acid, acrylamide, perfluoropolyether methacrylate and carbon quantum dot-titanium dioxide composite by a high-pressure homogenizer for 45-100 minutes to obtain a pre-emulsion; S2: Add the remaining 2 / 3 of the emulsifier and 1 / 2 of the initiator into deionized water, raise the temperature to 60-90°C, then drop the pre-emulsion and the remaining 1 / 2 of the initiator to carry out a polymerization reaction to obtain a modified styrene-acrylic emulsion.

Citation Information

Patent Citations

  • Styrene-acrylate emulsion with hydrophobic oleophylic fluorine-silicon-modified nuclear shell structure and preparation method thereof

    CN102060952A

  • Anti-fake material composition based on fluorescent quantum dots and use method thereof

    CN105778725A